Prevalance of BRCA1 and BRCA2 mutations in familial breast cancer patients in Lebanon - Jalkh Nadine; Nassar-Slaba Jinane; Chouery Eliane; Salem Nabiha; Uhrchammer Nancy; Golmard Lisa; Stoppa-Lyonnet Domique; Bignon Yves-Jean; Mégarbané André (Hereditary Cancer in Clinical Practice, 2012)
Abstract Breast cancer is the most prevalent malignancy in women in Western countries, currently accounting for one third of all female cancers. Familial aggregation is thought to account for 5–10 % of all BC cases, and germline mutations in BRCA1 and BRCA2 account for less of the half of these inherited cases. In Lebanon, breast cancer represents the principal death-causing malignancy among women, with 50 % of the cases diagnosed before the age of 50 years. In order to study BRCA1/2 mutation spectra in the Lebanese population, 72 unrelated patients with a reported family history of breast and/or ovarian cancers or with an early onset breast cancer were tested. Fluorescent direct sequencing of the entire coding region and intronic sequences flanking each exon was performed. A total of 38 BRCA1 and 40 BRCA2 sequence variants were found. Seventeen of them were novel. Seven confirmed deleterious mutations were identified in 9 subjects providing a frequency of mutations of 12.5 %. Fifteen variants were considered of unknown clinical significance according to BIC and UMD-BRCA1/BRCA2 databases. In conclusion, this study represents the first evaluation of the deleterious and unclassified genetic variants in the BRCA1/2 genes found in a Lebanese population with a relatively high risk of breast cancer.